2017
DOI: 10.1103/physrevd.96.024042
|View full text |Cite
|
Sign up to set email alerts
|

Particle collision with an arbitrarily high center-of-mass energy near a Bañados-Teitelboim-Zanelli black hole

Abstract: We consider a particle collision with a high center-of-mass energy near a Bañados-TeitelboimZanelli (BTZ) black hole. We obtain the center-of-mass energy of two general colliding geodesic particles in the BTZ black hole spacetime. We show that the center-of-mass energy of two ingoing particles can be arbitrarily large on an event horizon if either of the two particles has a critical angular momentum and the other has a non-critical angular momentum. We also show that the motion of a particle with a subcritical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 58 publications
(60 reference statements)
2
19
0
Order By: Relevance
“…For the extremal case, we have found that the particles with critical angular momentum can only exist on the degenerate horizon. The above arguments show that the motion and collision of particles in the linear dilaton black hole has a similar behavior to the observed for the motion and collision of particles in the BTZ black hole [43][44][45][46]. Also, we showed that in the equatorial plane the string coupling depends on r 0 and it does not depend on a.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…For the extremal case, we have found that the particles with critical angular momentum can only exist on the degenerate horizon. The above arguments show that the motion and collision of particles in the linear dilaton black hole has a similar behavior to the observed for the motion and collision of particles in the BTZ black hole [43][44][45][46]. Also, we showed that in the equatorial plane the string coupling depends on r 0 and it does not depend on a.…”
Section: Discussionsupporting
confidence: 83%
“…(97), whose derivative evaluated on the internal horizon r − is positive dR c dr | r=r− > 0; therefore, the particle with critical angular momentum can reach the inner horizon and the CM energy can be arbitrarily high, with the BSW process being possible on the inner horizon. This behavior is similar to the rotating BTZ black hole [44][45][46]. In Table I we show the behavior of the CM energy on the inner horizon as a function of the angular momentum L 1 of a particle, we observe that when L 1 approaches to the critical angular momentum L c = r0r−E a , the CM energy increases and tends to infinity when L 1 → L c .…”
Section: The CM Energy Of Two Colliding Particlessupporting
confidence: 61%
See 2 more Smart Citations
“…Shortly after the BTZ black hole in three-dimensional spacetime was discovered [1,2], its geodesic structure was studied in detail [3,4]. The study of those geodesics not only gave insight into the geometrical properties of the BTZ spacetime, but also led to some interesting applications [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%